PENGARUH SAP BERBASIS AKRUAL, SISTEM INFORMASI AKUNTANSI, KUALITAS SDM, PENGENDALIAN INTERNAL DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN DI BADAN NASIONAL PENANGGULANGAN BENCANA - Franta Eveline (Media Riset Akuntansi, Auditing & Informasi, 2016)
This Study objectives are to test the influence of Accrual Based – Government Accounting Standard, Accounting Information System, Human Resourching Quality, Internal Control, and Organizational Commitment affect the quality of Ministry/Board financial statements especially in National Board of Disaster Management (BNPB). This study population is the stakeholders of National Board of Disaster Management financial statement consisting of Authorized Budget User, Financial Bureau, Expenditure Treasurer, Assistant of Expenditure Treasurer, Commitment-Making Officer, and Internal Auditor in BNPB. Sample is determined by using Proportionate Stratified Random Sampling techniques. Using the Likert measurement scale and Inferensial Parametris data analysis. The hypothesis is tested comparatively. The result showed that The  Impplementation of Accrual Based – Government Accounting Standard have a significant effect on the quality of financial statement, Impplementation of Accounting Information System have a significant effect on the quality of financial statement, Human Resourching Quality have a significant effect on the quality of financial statement, Internal Control have a siginificant effect on the quality of financial statement, and Organizational Commitment have a significant effect on the quality of financial statement. The maximum implementation of Accrual Based – Government Accounting Standard, Accounting Information System, Human Resorching Quality, Internal Control and Organizational Commitment will increase as well as the quality of financial statement in BNPB.Keywords: Accrual Based – Government Accounting Standard, Accounting Information System, Human Resourching Quality, Internal Control, Organizational Commitment, National Board of Disaster Management.